PEMANFAATAN SUMBER DAYA LOKAL DALAM KEGIATAN DEMONSTRASI MASAK DAN PMT UNTUK PENCEGAHAN STUNTING DI KELURAHAN PANJI SARI - Soptiana, Hesti; Putri, Hari Tri Prasetio Anggraeny; Agisna, Lalu Alfan Mugni; Rusyda, Annida Puteri Naajiha; Hasanah, Elyatul; Afriani, Fauziah; Atikha, Luqyana Salsabila; Putra, Nathanael Lucky Hadi; Umam, Maslihul; Sufrafti, Lasmi (Universitas Mataram, 2024)
The Community Real Work Program (KKN PMD) is an educational program that provides students with direct experience in identifying and overcoming community problems by practicing the knowledge they have gained on campus. In this program, Mataram University students implemented the